2008
DOI: 10.1111/j.1365-2710.2008.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-linear relationship between total and unbound serum concentrations of valproic acid in epileptic children

Abstract: A regression equation for estimation of the unbound VPA concentration, based on total VPA concentration collected during routine therapeutic drug monitoring was established. Use of two additional antiepileptics and ethosuximide treatment was considered as potential factors affecting unbound VPA concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Several other groups (Imai et al 2003;Roh et al 2004;Watanabe et al 2005) have reported growth inhibition and sensitization to Fas-mediated cell death of human osteosarcoma cells by HDAC inhibitors, FR901228 and TSA, but not inhibition of soluble Fas secretion. Importantly, our results showed that VPA exerted its eVects at concentrations which are attainable in sera of patients administered with VPA orally without serious side eVects (Johannessen and Johannessen 2003;Chavez-Blanco et al 2005;Allen et al 2006;Ueshima et al 2008). These results indicate the possibility that VPA may be applicable to the treatment of osteosarcomas.…”
Section: Discussionmentioning
confidence: 54%
“…Several other groups (Imai et al 2003;Roh et al 2004;Watanabe et al 2005) have reported growth inhibition and sensitization to Fas-mediated cell death of human osteosarcoma cells by HDAC inhibitors, FR901228 and TSA, but not inhibition of soluble Fas secretion. Importantly, our results showed that VPA exerted its eVects at concentrations which are attainable in sera of patients administered with VPA orally without serious side eVects (Johannessen and Johannessen 2003;Chavez-Blanco et al 2005;Allen et al 2006;Ueshima et al 2008). These results indicate the possibility that VPA may be applicable to the treatment of osteosarcomas.…”
Section: Discussionmentioning
confidence: 54%
“…In fact, there have been several studies on the estimation and/or a regression equation to predict the unbound from the total concentration. [9][10][11] However, as revealed in our previous study, the equation for epileptic children or adult patients is not applicable for epileptic infants aged less than 1 year old. The unbound serum VPA concentrations in infants vary patient by patient more markedly than those in children, and, thereby, their total and unbound VPA concentrations are poorly correlated (Fig.…”
mentioning
confidence: 93%
“…2). Lastly, the predicted value calculated with Model 85 was compared with the value calculated using the previously reported equation, 11) indicating that the prediction improves and the variability of the prediction is smaller when the calculation is performed with Model 85 (Fig. 3).…”
Section: Characterization Of the Serum Unbound Vpa Concentration Profmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have focused therefore on the free concentrations or free fraction of AEDs (e.g. carbamazepine [26], phenytoin [27], and valproate [28]). In these publications, the free plasma concentration of the drug was found to better reflect the concentrations of the extracellular space (ECS) and the brain's interstitial fluid.…”
Section: Pharmacokineticsmentioning
confidence: 99%